EXISTENCE OF CO-WORKING SPACE TO SUPPORT LOCAL INDUSTRIES IN SAMARINDA - Gilang Mukti Rukmana; Khoirul Amin; Asmadhini Handayani Rahmah; Joko Sabtohadi (Jurnal Scientia, 2023)
The presence and progress in the fields of technology, information, and communication due to the influence of globalization make it easy for professional workers to do various jobs, especially to achieve work effectiveness, time efficiency and interact with a wider network. Co-Working Space is present as a forum that facilitates the needs of professional workers as well as new innovations in the contemporary work world. This study aims to analyze the role of local Co- Working Space in supporting the growth of creative industries in Samarinda. While the long- term goal of this research was to find out the strategies carried out by Co-Working Space in accommodating professional workers in Samarinda to be able to compete and to contribute to the growth of industry 4.0, both locally and internationally. This research used qualitative research methods that combined literature review and interviews with Co-Working Space industry. This research was targeted to have output in the form of references and collaborative programs related to the application of the Co-Working Space system at Universitas Muhammadiyah Kalimantan Timur.